Contemporary Business Environment and Contemporary Techniques - Annisa Zalzatu Rahma; Ahmad Nadhif Qulub; Wahyu Prasetyo; Nurul Amelia Rizqi R; Ahmad Sodiq (PT. Padang Tekno Corp, 2024)
The current business environment is experiencing rapid change influenced by technology, globalization, and changes in consumer behavior. A deep understanding of this environment is important for a company's adaptation. An important development driving changes in the contemporary business environment at large is the growth of markets and international trade. Today's contemporary business is characterized by increasingly fierce competition, rapid innovation, and constant change. To face this increasingly complex business environment, many contemporary techniques are used by companies, such as information technology, risk management, and supply chain management. These techniques help companies to stay competitive and adapt to the rapidly changing business environment. This research is expected to provide a better understanding of the contemporary business environment and contemporary techniques used in business today.